Characterization of the Niemann-Pick C pathway in alveolar type II cells and lamellar bodies of the lung - Roszell, Blair R. (American Physiological Society, 2012)
The Niemann-Pick C (NPC) pathway plays an essential role in the intracellular trafficking of cholesterol by facilitating the release of lipoprotein-derived sterol from the lumen of lysosomes. Regulation of cellular cholesterol homeostasis is of particular importance to lung alveolar type II cells because of the need for production of surfactant with an appropriate lipid composition. We performed microscopic and biochemical analysis of NPC proteins in isolated rat type II pneumocytes. NPC1 and NPC2 proteins were present in the lung, isolated type II cells in culture, and alveolar macrophages. The glycosylated and nonglycosylated forms of NPC1 were prominent in the lung and the lamellar body organelles. Immunocytochemical analysis of isolated type II pneumocytes showed localization of NPC1 to the limiting membrane of lamellar bodies. NPC2 and lysosomal acid lipase were found within these organelles, as confirmed by z-stack analysis of confocal images. All three proteins also were identified in small, lysosome-like vesicles. In the presence of serum, pharmacological inhibition of the NPC pathway with compound U18666A resulted in doubling of the cholesterol content of the type II cells. Filipin staining revealed a striking accumulation of cholesterol within lamellar bodies. Thus the NPC pathway functions to control cholesterol accumulation in lamellar bodies of type II pneumocytes and, thereby, may play a role in the regulation of surfactant cholesterol content.